2012
DOI: 10.1007/s11230-011-9341-8
|View full text |Cite
|
Sign up to set email alerts
|

Descriptions of eight new species of Ligophorus Euzet & Suriano, 1977 (Monogenea: Ancyrocephalidae) from Red Sea mullets

Abstract: Eight new species of Ligophorus Euzet & Suriano, 1977 (Monogenea: Ancyrocephalidae) are described from two species of mullets from the Red Sea. Ligophorus bykhowskyi n. sp. and L. zhangi n. sp. from Crenimugil crenilabris (Forsskål) differ from other species of the genus in the structure of the male copulatory organ, which has a simple accessory piece and a wide copulatory tube that arises from a large, single-chambered, expanded base. Ligophorus simpliciformis n. sp., L. bipartitus n. sp., L. campanulatus n. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…L -Thylodelphys clavata; M, N, O -Neoechinorhychus agilis; P, Q, R -Ergasilus lizae Scale bars: M -500 µm; L, O, P -100 µm; N, Q -50 µm; R -20 µm expanded by Rubtsova et al (2006) on M. cephalus in the Black and Azov Seas. Ligophorus cephali has also been reported to be specific to M. cephalus in different sampling areas (Rubtsova et al, 2006;Dmitrieva et al, 2009a,b;Dmitrieva et al, 2012). Both, Ligophorus cephali and L. mediterraneus are the first records for Turkish parasitic fauna in fish as well.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…L -Thylodelphys clavata; M, N, O -Neoechinorhychus agilis; P, Q, R -Ergasilus lizae Scale bars: M -500 µm; L, O, P -100 µm; N, Q -50 µm; R -20 µm expanded by Rubtsova et al (2006) on M. cephalus in the Black and Azov Seas. Ligophorus cephali has also been reported to be specific to M. cephalus in different sampling areas (Rubtsova et al, 2006;Dmitrieva et al, 2009a,b;Dmitrieva et al, 2012). Both, Ligophorus cephali and L. mediterraneus are the first records for Turkish parasitic fauna in fish as well.…”
Section: Discussionmentioning
confidence: 97%
“…Here in the present study, two species of Ligophorus and one species of Microcotyle were identified. Twelve species of Ligophorus are strictly specific to mugilids; including Ligophorus cephali and L. mediterraneus on Mugil cephalus (Sarabeev et al, 2005;Dmitrieva et al, 2012). There are several reports of only Microcotyle mugilis parasitizing golden grey mullet, and there is no report on Ligophorus cephali and L. mediterraneus on this fish species at present (see Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The monogeneans found herein have been reported in several mugilids (see Table 1). Strict host-specificity is a common phenomenon among monogeneans, and all species of Ligophorus are strictly specific to mugilids, including L. cephali and L. mediterraneus which are specific to M. cephalus (Sarabeev et al 2005;Dmitrieva et al 2012). The known geographical and host range of L. mediterraneus has been expanded by subsequent records on M. cephalus in the Black and Azov Seas (Rubtsova et al 2006).…”
Section: Discussionmentioning
confidence: 99%